(untitled) (PUSA Journal of Hospitality and Applied Sciences, 2022)
Background: The hotels industry has brought in tremendous changes in its hospitality standards and services since its origin. The success of this industry depends on how much their customer is happy with the services and how much more they can offer to their guests. Gender equality has encouraged single lady traveler for work, leisure, health etc. Many hotels does not cater to this gender preferred services though, women friendly frills have become an international trend and since the last decade the hotels in India are also gearing up to tap this clientele. Objective: To understand the scope of single lady travelers market in terms of its productivity. Methodology: This study falls within a quantitative research approach. Data collection was done by random probability sampling from subjects those who have been travelling frequently and have been in house-guest of five star hotels in Delhi/NCR. The sample size was 100. They were the repeat guests in the age group of 18-50 years. Questionnaire was used as a part of the research tool. Analysis was done using the percentage parameter. Results: Of the total participants 64.3% of the guests taken into account were male, 34.8% were female and 0.9% were others. The scope of the market is promising in the coming five years of the future about 81.7% of the respondents believed that such initiative by the hotels will make a difference for the single lady travelers. 78.3% of women would avail this facility while travelling alone. In developing countries about 73% of respondents both male & female were aware of this initiative and were positive and industrial about it. Conclusion: Women prefer hotels that incorporate features that are women centric. With the growing concerns on safety of single lady travelers, the hospitality industry in India is seen to be doing their bit to cater to the ‘ladies’ demand and ensure their security.